2016
DOI: 10.5465/ambpp.2016.11152abstract
|View full text |Cite
|
Sign up to set email alerts
|

"Transformational Leadership, High Performance Work Practices, and an Effective Organization"

Abstract: Although transformational leadership is touted as an important approach for improving employee well-being and an effective organization, very little is known about how its key principles can be manifested through specific Human Resource Management (HRM) systems. This is unsatisfactory as leadership is pertinent to the management of human resources and many HRM researchers and practitioners would benefit from a theoretical understanding of how effective leadership principles can be strengthened by HRM systems.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Zhu et al (2005) supported the theoretical relevance between TL and HR and explained that leaders formulate a common vision and communicate it through HR practices and policies. Leaders are capable enough of achieving HR effectiveness that encourages individuals to learn new skills or capabilities that ultimately contribute towards their growth and development (Ogbonnaya & Nielsen, 2016).…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhu et al (2005) supported the theoretical relevance between TL and HR and explained that leaders formulate a common vision and communicate it through HR practices and policies. Leaders are capable enough of achieving HR effectiveness that encourages individuals to learn new skills or capabilities that ultimately contribute towards their growth and development (Ogbonnaya & Nielsen, 2016).…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
“…Despite the growing interest of leaders with respect to HR, the empirical evidence that explores the mediating role of perceived HR effectiveness between TL and organisational learning is scarce (Ogbonnaya & Nielsen, 2016). Previous research findings indicate the association between TL and HR practices (Hassan et al, 2019; Manshadi et al, 2014).…”
Section: Literature Review and Theoretical Modelmentioning
confidence: 99%
“…To assess which antecedents are predictive of the resulting profiles, we conducted a multinomial regression analysis using the package Nnet (v.7. [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. This analysis compared the likelihood of an employee being a member of a certain profile with a referent group based on a specific antecedent.…”
Section: Analysesmentioning
confidence: 99%
“…Empirical studies have demonstrated that high happiness well-being (e.g., employees' satisfaction with their work) and performance can go handin-hand [6,7]. Other studies, however, have shown that organizations striving to improve their performance may also increase work intensity, which (unintentionally) negatively affects employee health well-being (e.g., exhaustion) [2,7,8]. This indicates that simultaneously promoting happiness and health well-being, while stimulating job performance is a challenging endeavor for organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Followers are encouraged to participate in identifying required change and how to achieve it (Bass 1997 ), to see deeper purpose in their work and exceed their own self-interests for the good of the organisation and to consider the needs of others over their own, share risks with others and conduct themselves ethically. Transformational leaders provide personalised consideration on individual needs for achievement, development, growth and support and adopt coaching and mentoring strategies in their relationships with followers (Bass and Steidlmeier 1999 ; Dong et al 2017 ; Brodbeck et al 2002 ) and have positive expectations of the team members (Ogbonnaya and Nielsen 2016 ). The leader is naturally enthusiastic and capable of convincing members that they can deliver up to their potentials because she/he believes they are talented and willing to work and utilises whatever rewards are available (Ahmad et al 2014).…”
Section: Annex 111: Characteristics Of Leadership Personae Required mentioning
confidence: 99%